In situ PXRD analysis on the kinetic effect of PVP-K90 and PVCap on methane hydrate dissociation below ice point - Zhou, Xuebing; Zhang, Qian; Long, Zhen; Liang, Deqing (Fuel, 2021)
Kinetic hydrate inhibitors (KHIs) have been developed as an alternative for the prevention of hydrate plug in natural gas transportations due to economic and environmental factors. To understand the kinetic performance of KHIs comprehensively, dissociations of CH4 hydrates in the presence of PVP-K90 and PVCap were investigated below ice point. Cryo-SEM and in situ PXRD were used to provide a microscopic insight on the dissociation kinetics. Results showed that a typical CH4 hydrate dissociation at 268 K could be divided into 4 stages. The selfpreservation effect took place in the second stage accompanied with an rise in the ratio of Ih(002) to Ih(100) peaks from 0.5 to 1.1. About 30% of CH4 hydrates were suggested to dissociate into plate-like ice to form ice coatings on hydrate surface. In the presence of PVP-K90 or PVCap, the self-preservation stage reduced greatly and the initial dissociation rates of CH4 hydrates were found enhanced as the concentrations of the KHIs increased from 0.5 to 2.0 wt%. SEM images revealed that PVP-K90 was suggested to be included in the small ice crystals embedded in hydrate phase and hinder the connections of the plate-like ice crystals on hydrate surface, while PVCap was found to induce a dendritic growth of CH4 hydrate, leading to a surge in the specific surface area of CH4 hydrates which was not beneficial to the formation of ice coatings on hydrate phase. Therefore, both PVP-K90 and PVCap promoted hydrate dissociation below ice point by inhibiting the formation of selfpreservation effect.